Stilistika dalam 'aurad al-yaum wa laylah' karya Ibnu Arabi - Delami Delami; Ferry Syahputra (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
This stylistic research aims to look at the style of language used by Ibn 'Arabi in his work entitled "Awrad al-Yaum wa laylah". The problem raised in this study is to look at the diction tendencies used by Ibn Araby in his work. The purpose of this study is to describe Mahyudin ibn Araby's diction contained in his essay "awrad al-yaum wa laylah". This study used a descriptive qualitative method with note-taking techniques. Thus, it can be obtained the research results of the diction form chosen by ibn 'Araby in the work "Aurad al-yaum wa laylah", after analyzing the data it is found; The language style is used by Ibn 'Araby, 5 Erotica, 15 Metaphor, 8 Repetition, 2 inversion, 1 rhetoric and 2 apophasis.